Audiotactile interactions in near and far space. - Kitagawa, N; Zampini, M; Spence, C (2005)
In this study we investigated audiotactile spatial interactions in the region behind the head. In experiment 1, participants made unspeeded temporal order judgments (TOJs) regarding pairs of auditory and tactile stimuli presented at varying stimulus onset asynchronies (SOAs) using the method of constant stimuli. Electrocutaneous stimuli were presented to the left or right earlobe while auditory stimuli were presented from just behind the participant's head on either the same or opposite side. Participants responded significantly more accurately when the stimuli were presented from different sides rather than from the same side. In experiment 2, we used a distractor interference task to show that speeded left/right discrimination responses to electrocutaneous targets were also modulated by the spatial congruency of auditory distractors presented behind the head. Performance was worse (i.e. response latencies were slower and error rates higher) when the auditory distractors were presented on the opposite side to the electrocutaneous target than when they were presented on the same side. This crossmodal distractor interference effect was larger when white noise distractors were presented from close to the head (20 cm) than when they were presented far from the head (70 cm). By contrast, pure tone distractors elicited a smaller crossmodal distractor interference effect overall, and showed no modulation as a function of distance. Taken together, these results suggest that the spatial modulation of audiotactile interactions occurs predominantly for complex auditory stimuli (for example, white noise) originating from the region close to the back of the head.